Biochemical characterization of antioxidant in selected Iranian honey / Saleh Saleh Nezhad - Saleh Saleh, Nezhad (2013)
The physicochemical parameters of eight Iranian honey samples from different botanical origins were characterized in this study. Differences in pH, moisture, sugar profiles and phenolic profiles were observed. Iranian honeys contain different carbohydrate structures. The relationship between different parameters such as phenolic concentration, colour, antioxidant properties, moisture content and hydroxymethylfurfural (HMF) content were established. High correlations between total phenolic content and radical scavenging properties, moisture content and antioxidant properties were also observed for all the samples. The correlation between HMF content and honey colour was observed within the eight types of honeys. Some antioxidants are potential floral origin markers of honey and Determination of polyphenolics find to be suitable for quality control and biochemistry analysis of natural honey samples. They contribute to physicochemical properties of honey and fulfill human health. A high positive correlation was found between the two assays for antioxidant activities of honeys, and their phenolic content, indicating the contribution of phenolics in the antioxidant activities of honey although there may be other minor factors contributing to the antioxidant effects of honey. There is linear correlation between water content and antioxidant activities. The antioxidant activities and phenolic content differed amongst the honey samples possible due to their different floral sources. The Iranian honey also showed potential anti-proliferative effects against the breast cancer cells, MCF-7 and MDA MB 231. Saffron honey showed strong anti-proliferative effects and its high phenolic content could be a contributing factor. When the honey sample was added to broilers’ feed in a feeding study, there was no significant difference in feed intake, weight gain, feed to gain ratio and weight of gastrointestinal tract, abdominal i fat, liver, spleen and pancreas in the animal model. Several chromatographic techniques were applied to separate and detect the presence of polyphenols in the honey samples. The most important classes of antioxidant polyphenols are flavanone, flavone, flavan, flavonols and phenolic acids. The characterization of polyphenols depends on the method of identification. These polyphenols can be considered as a botanical marker and was tentatively characterised by HPLC-DAD, HPLCMS/MS, GCMS and LC-MSTOF. This study shows that ITTOF is the best instrument for analysis of polyphenols in the honeys. The results obtained indicated possible markers for honey type authentication by different analysis. Apigenin (41.74 ng/100 μl) and quercetin (3.38 ng/100 μl) as potential bioactive markers present in saffron honey are found in high quantities. Available literature indicates that no previous studies on antioxidant property have been done on Iranian honeys. This is the first study to evaluate the antioxidant properties of selected Iranian honeys and may provide useful data for their potential medicinal uses.